STUDY OF THE IMPLEMENTATION OF VETERINARY CONTROL NUMBER IN MEAT PROCESSING COMPANIES IN DENPASAR CITY - Mandari, Elis; Rudyanto, Mas Djoko; Agustina, Kadek Karang (Buletin Veteriner Udayana; Vol. 14 No. 2 April 2022DO - 10.24843/bulvet.2022.v14.i02.p14, 2022)
This study aim was to review the implementation of Veterinary Control Number (NKV) on five companies in Denpasar city on a small, medium and large scale. A total of five meat processing companies in the city of Denpasar carried out in the study of the application of NKV through guided assessments using a questionnaire sourced from the Indonesian Minister of Agriculture with Regulation Number 318/KPTS/OT.140/10/2005. The results showed that the meat processing companies, namely PT. Aromaduta Rasaorima, Titilestari, CV. Dwi Boga Utama and UD. Asa Barokah Mandiri have applied the NKV process of Level 2, which means that it still has the right to obtain NKV in good category (towards export qualifications). Whereas UD. Budi in this study has applied the NKV process of Level 3, which means that they still has the right to obtain an NKV with sufficient categories. The results above show that meat processing companies in Denpasar need to optimize the application of NKV standards in order to achieve a better level.